Pure online program : crossing boundaries , engaging minds - Kaur, Abtar; Lim , Tina Swee Kim; Zoraini Wati Abas (2010)
This PowerPoint presentation on Pure online program : crossing boundaries , engaging min'ds' presented during OUM Seminar Series 05/2010 on 14 May 2010 at OUM Theatrette.